The social networks of public universities in Andorra, Spain and France: Study and analysis of the social networks of public universities in Andorra, Spain and France - Pérez-Bonaventura, Marc; Fortó-Areny, Josep; Mariño-Mesías, Rosa M. (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Nowadays, universities need digital marketing and social media strategies to reach their potential students. This article focuses on public universities in Andorra, north-eastern Spain, and south-eastern France. It investigates how these institutions are acting in social networks through an observational, analytical and comparative study between them. Important differences are observed between the universities of different countries at the level of use and results in social media. Universities of Catalonia stand out in all the results and that of Andorra does so in relative values with respect to their number of students.